Enter to Neo-Realist Era? Major Trends of Nepali Diplomacy in Federal Republic Era - Adhikari, Narayan; Thapa, Manoj (Journal of APF Command and Staff College, 2020)
Nepal entered to federal republic era after promulgation of new constitution in 2015. An alliance of communist parties – now unified into a single party, Nepal Communist Party (NCP) – obtained nearby two-third majority in 2017 legislative election. Four major diplomatic activities of in this new era are remarkable: frequent visit of high level delegates to Nepal, diversification of foreign relations, military exchange in bilateral and multilateral sector, and active participation in strategic projects of global superpowers. Where Nepal is emphasizing in its foreign relations? What is the Nepal government's interpretation with new changes? This study examines these questions to identify and access Nepal's contemporary foreign policy. It, moreover, examines whether we can interpret these change based on (neo) realist perspective - a predominant worldview in interpreting Nepal's role and position in international relations.